First report of a nano‐Cu2O‐catalyzed protocol for homo‐coupling reaction of terminal alkynes in water/ionic liquid medium. (13th June 2016) - Tang, Bo‐Xiao; Fang, Xiao‐Niu; Kuang, Ren‐Yun; Wu, Jian‐Hong; Chen, Qiao; Hu, Shao‐Jun; Liu, Yi‐Lin
Abstract : A new, efficient and green protocol for the nano‐Cu2 O‐catalyzed homo‐coupling reaction of terminal alkynes has been developed, using water/ionic liquid as an environmentally friendly solvent. Moreover, the system also allows the synthesis of unsymmetric 1, 3‐diynes bycross‐coupling of two different terminal alkynes. It is noteworthy that the nano‐Cu2 O‐catalyzed methodology is a good supplement to copper catalyst for the Glaser‐type homo‐coupling reaction. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A new, efficient and green protocol for the nano‐Cu2 O‐catalyzed homo‐coupling reaction of terminal alkynes has been developed, using water/ionic liquid as an environmentally friendly solvent. The nano‐Cu2 O‐catalyzed methodology is a good supplement to copper catalyst for the Glaser‐type homo‐coupling reaction.